PENGARUH BRAND AWARENESS , BRAND IMAGE DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMAKAIAN JASA PADA MASKAPAI PENERBANGAN GARUDA INDONESIA - Isna Armawati; Saryadi Saryadi; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2014)
Garuda Indonesia is Indonesian government-owned airlines that always provide the best quality services to its passengers, starting from purchase the ticket until post-flight. Garuda Indonesia proves their service quality of being recognized in international standard by joining the Sky Team alliance and awarded for top brand index every year. Although always placed in the first rank in 2012 until 2014 but the index percentage continues to decline. Garuda Indonesia’s Touch Points service also becomes a measurement regarding level of image and perceived quality towards the company.The purpose of this research is to examine the influence of brand awareness, brand image and perceived quality on customer buying decision in Garuda Indonesia Airlines. The type of this research is explanative research. The method of collecting data using interviews, literature study and questionnaire. The technique of sampling using purposive sampling. The sample in this research were 100 respondents who are the customers in Garuda Indonesia Branch Office Semarang. Measurement scale using Likert Scale. Quantitative analysis uses validity test, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, and a significant test (t and F) using SPSS 15.0.Based on the data analysis found in partial, the variable of brand awareness  has contribution influence on buying decisions of 21,1%, the variable of brand image has contribution influence on buying decisions of 51,4%, and the variable of perceived quality has contribution influence on buying decisions of 58,4%. Simultaneously the variable of brand awareness, brand image and perceived quality has contribution influence on buying decisions of 64,6%.Based on the research results, the researcher suggests that the company should improve the delivery of the information regarding promotion in media communication, paying attention to every service at customer’s touch points in order for customer to be able to utilize the service and facilities that offered as well as avoid delays flight hours especially for domestic routes